On Some Applications of Information Indices in Chemical Graph Theory - Konstantinova, E. V. (General Theory of Information Transfer and Combinatorics, 2006)
Information theory has been used in various branches of science. During recent years it is applied extensively in chemical graph theory for describing chemical structures and for providing good correlations between physico–chemical and structural properties by means of information indices. The application of information indices to the problem of characterizing molecular structures is presented in the paper. The information indices based on the distance in a graph are considered with respect to their correlating ability and discriminating power. Mathematics Subject Classification 2000: 94A15, 94A17, 94C15.